2017
DOI: 10.1038/s41598-017-12665-0
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFII is required for morphogenesis of the neural crest-derived tympanic ring

Abstract: Chicken Ovalbumin Upstream Promoter-Transcription Factor II (COUP-TFII) plays pivotal roles in cell growth, cell differentiation, and cell fate determination. Although genome-wide studies have identified COUP-TFII binding on gene sets mainly involved in neural crest cell (NCC) development and craniofacial morphogenesis, the direct functional connection between COUP-TFII and NCCs in vivo has not been well characterized. In this study, we show that COUP-TFII is expressed in the subpopulation of NCCs and its deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…Single Nr2f1 mutants die perinatally without overt craniofacial abnormalities (Qiu et al, 1997), while Nr2f2 mouse mutants die with angiogenic and cardiac defects by E10.5 (Pereira et al, 1999). A recent study has shown that conditional mutation of Nr2f2 within NCCs results in ectopic Sox9 expression and abnormalities in the tympanic ring (Hsu et al, 2017), a proximal first arch-derived dermal bone (Mallo, 2001, Hsu et al, 2017), consistent with our finding that Nr2fs inhibit maxillary sox9a expression in fish. Deletions spanning the NR2F1 and NR2F2 genomic loci have also been identified in isolated human patients with craniofacial anomalies (Poot et al, 2007, Brown et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Single Nr2f1 mutants die perinatally without overt craniofacial abnormalities (Qiu et al, 1997), while Nr2f2 mouse mutants die with angiogenic and cardiac defects by E10.5 (Pereira et al, 1999). A recent study has shown that conditional mutation of Nr2f2 within NCCs results in ectopic Sox9 expression and abnormalities in the tympanic ring (Hsu et al, 2017), a proximal first arch-derived dermal bone (Mallo, 2001, Hsu et al, 2017), consistent with our finding that Nr2fs inhibit maxillary sox9a expression in fish. Deletions spanning the NR2F1 and NR2F2 genomic loci have also been identified in isolated human patients with craniofacial anomalies (Poot et al, 2007, Brown et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…For example, in the human endometrium, COUP-TF2 is a positive regulator of the pro-ovary WNT4 gene and in mice Coup-tf2 negatively regulates the expression of the pro-testis Sox9 gene in the osteogenic mesenchyme. 29 , 30 …”
Section: Main Textmentioning
confidence: 99%
“…For example, in the human endometrium, COUP-TF2 is a positive regulator of the pro-ovary WNT4 gene and in mice Coup-tf2 negatively regulates the expression of the pro-testis Sox9 gene in the osteogenic mesenchyme. 29,30 In addition to revealing unforeseen mechanisms in sex development, our study also highlights the importance of nuclear receptors (NR) in human development and disease. Humans have 48 different NRs with a diverse range of functions and next-generation sequencing approaches are starting to identify novel and sometimes unexpected phenotypes associated with specific NR variants.…”
mentioning
confidence: 80%